DYNAMICS OF HEALTH DISORDERS IN EMPLOYEES OF MODERN CHEMICAL ENTERPRISES - N. M. Meshchakova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
We revealed, the peculiarities of health, disorders in the employees of modern, chemical enterprises in the dynamics of medical examinations and quantitative risk assessment of the basic pathological syndromes. It was determined, that significant growth, of cases of medium, and. high, risk of functional disorders of cardiovascular system, boundary psychical disorders, gastrointestinal tract and. liver was observed in dynamics. We registered the increase of levels of morbidity of circulatory system, nervous system, and. psychiatric disorders. Reliable increase of risk levels associated, with, exposure toxic load, in workers of the basic professions in caustic soda and. polyvinyl chloride productions was detected.